Etika dan Profesionalisme Wartawan Serambi Indonesia dan Rakyat Aceh Dalam Peliputan Pelanggaran Syariat Islam di Provinsi Aceh - Darmadi (Budapest International Research and Critics University, 2017)
This article explains about the ethics and professionalism of journalists atSerambi Indonesia daily and Rakyat Aceh (People of Aceh) in conducting acoverage of violations of Islamic Sharia in Aceh. The ethics of journalists ofboth media can be seen through the implementation of the code ofjournalistic ethics maximally in the coverage of violations of Islamic Shari'ahthat implies the principle of presumption of innocence, put forward theaccuracy of news, to make every news can be balanced so that the news ofviolation of Islamic Shari'a can be objective, safeguarding the privacy rightsof perpetrators and victims and applying Islamic communication ethics andthe principle of da'wah journalism